The Conceptual Basis of the Tourism and Hospitality Industry’s Development - KONOVALOVA, Elena Evgenievna; YUDINA, Elena Vladimirovna; LAGUSEV, Yuri Mikhailovich; SHALAEV, Dmitry Viktorovich; RASSOKHINA, Tatiana Vasilyevna (Journal of Environmental Management and Tourism, 2019)
The article is devoted to the elaboration of the conceptual basis of the tourism and hospitality industry’s development. It has been established that the extension of the tourism and hospitality industry into other service sectors has become one of the consequences of diversification of the tourism and hotel service market. It has been proved that various specialized businesses manufacturing diverse components and types of tourism and hotel products have appeared. It has been determined that information technologies result in the formation of a unified information space where every enterprise and every consumer finds a niche of their own and forms their network of ties. It has been found that the tourism and hospitality industry’s transition into a new technological space becomes one of the most important signs of the formation of the innovative paradigm of its development that is based on principles of ecologization, socialization and humanization that will eventually improve its efficiency.